Applications of computational intelligence : Second IEEE Colombian Conference, ColCACI 2019, Barranquilla, Colombia, June 5-7, 2019, Revised Selected Papers /: Second IEEE Colombian Conference, ColCACI 2019, Barranquilla, Colombia, June 5-7, 2019, Revised Selected Papers. (2020) - Unknown
No abstract available